Skeletal Muscle Tissue Saturation Changes Measured Using Near Infrared Spectroscopy During Exercise Are Associated With Post-Occlusive Reactive Hyperaemia - Jones, Siana; Tillin, Therese; Williams, Suzanne; Rapala, Alicja; Chaturvedi, Nishi; Hughes, Alun D. (Frontiers in Physiology, 2022)
Measuring local haemodynamics in skeletal muscle has the potential to provide valuable insight into the oxygen delivery to tissue, especially during high demand situations such as exercise. The aim of this study was to compare the skeletal muscle microvascular response during post-occlusive reactive hyperaemia (PORH) with the response to exercise, each measured using near-infrared spectroscopy (NIRS) and to establish if associations exist between muscle measures and exercise capacity or sex. Participants were from a population-based cohort study, the Southall and Brent Revisited (SABRE) study. Skeletal muscle measures included changes in tissue saturation index at the onset of exercise (∆TSIBL-INC) and across the whole of exercise (∆TSIBL-EE), time to 50%, 95% and 100% PORH, rate of PORH recovery, area under the curve (AUC) and total oxygenated Haemoglobin (oxy-Hb) change during PORH. Exercise capacity was measured using a 6-minute stepper test (6MST). Analysis was by multiple linear regression. In total, 558 participants completed the 6MST with NIRS measures of TSI (mean age±SD: 73±7years, 59% male). A sub-set of 149 participants also undertook the arterial occlusion. Time to 100% PORH, recovery rate, AUC and ∆oxy-Hb were all associated with ∆TSIBL-EE (β-coefficient(95%CI): 0.05(0.01, 0.09), p=0.012; -47(-85, -9.9), p=0.014; 1.7(0.62, 2.8), p=0.002; 0.04(0.002,0.108), p=0.041, respectively). Time to 95% & 100% PORH, AUC and ∆oxy-Hb were all associated with ∆TSIBL-INC (β-coefficient(95%CI): -0.07(-0.12,-0.02), p=0.02; -0.03(-0.05, -0.003), p=0.028; 0.85(0.18, 1.5), p=0.013 & 0.05(0.02, 0.09), p=0.001, respectively). AUC and ∆Oxy-Hb were associated with steps achieved (β-coefficient(95%CI): 18.0(2.3, 33.7), p=0.025; 0.86(0.10, 1.6), p=0.027). ∆TSIBL-EE was associated with steps and highest VO2 (1.7(0.49,2.9), p=0.006; 7.7(3.2,12.3), p=0.001). ∆TSIBL-INC was associated with steps and VO2 but this difference was attenuated towards the null after adjustment for age, sex and ethnicity. ∆TSIBL-EE was greater in women (3.4(0.4, 8.9) versus 2.1(0.3, 7.4), p=0.017) and ∆TSIBL-INC was lower in women versus men (2.4(0.2, 10.2) versus 3.2(0.2, 18.2), p=0.016). Improved microvascular reactivity in response to ischaemia is associated with better vasodilatory capacity measured during exercise. These local microvascular NIRS-measures are associated with exercise capacity in older adults and several measures can detect differences in microvascular reactivity between a community-based sample of men and women.